Feasibility of Web-Based E-Book Learning Media Using Anyflip Web on Digestive System Materials - Nurdin Amin; Wati Oviana; Fildzah Ghassani (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
To improve human resources, one of the government's efforts is to make improvements in the world of education. One form of educational activity is the teaching and learning process between teachers and students. In order to achieve learning objectives in education, it is necessary to use learning media that supports one of the e-books that are in accordance with the demands of today's technology.The purpose of this study was to develop an e-book learning media and to test the feasibility of e-book media developed through validator experts and to find out the attractiveness of e-books for students. This study uses the type of R&D with the ADDIE model. The research sample consisted of 27 students in class XI IA4. The data collection instrument used validation sheets and student response sheets. The results of the validation by material experts obtained a score of 89% in the very feasible category, while the media validation was carried out in 2 stages. The first stage of media validation obtained a percentage of 76.36% in the appropriate category and the second stage of media validation obtained a score of 94% in the very feasible category. The results of the percentage score by the biology teacher obtained a score of 82.72% with a very decent category and the results of the student's response to the attractiveness of learning media obtained a percentage score of 88.64% with a very decent category, so that the use of web-based e-book media can increase students' activities and learning abilities.